Transdermal buprenorphine patch as an adjunct to multimodal analgesia after total joint arthroplasty: a retrospective cohort study - Fang, Xiaoli; Zhao, Yueping; Yao, Yao; Qin, Jianghui; Lin, Yan; Yang, Jin; Xu, Ruijuan (Frontiers in Pharmacology, 2024)
Background: Total hip arthroplasty or total knee arthroplasty (THA/TKA) is often associated with varying degrees of pain. In recent years, transdermal buprenorphine (TDB) patch has shown encouraging results for acute postoperative pain control in orthopedic surgery. The aim of our study was to investigate the efficacy and safety of the combination of TDB patch and nonsteroidal antiinflammatory drugs (NSAIDs) as a multimodal analgesic regimen after THA/TKA. Methods: Patients who underwent THA and TKA between January 2022 and January 2023 were reviewed. Three postoperative analgesic regimens were selected: Group A (flurbiprofen 50mg and tramadol 37.5 mg/acetaminophen 325 mg), Group B (flurbiprofen 50mg and TDB 5mg), and Group C (Parecoxib 40mg and TDB 5mg). The primary outcomes were the Wong-Baker face pain scale revision (FPS-R) scores and the rate of sleep disturbances. Secondary outcomes of the study included the proportion of patients with postoperative pain relief rates categorized as 0%, <50%, ≥50%, and 100%.Results: The dynamic FPS-R pain scores on day 3 after surgery in Group B were significantly lower than those in Group A for THA (P <0.017). The dynamic FPS-R pain scores were lowest in Group C on day 2 and 3 after THA and TKA (P <0.017). Rate of sleep disturbances was significantly lower in Group B for THA and in Group C for TKA, respectively, compared with that in Group A (P <0.017). The proportion of dynamic pain relief rate ≥50% in Group C was statistically higher than that in Group A for THA (P <0.017). Rate of adverse reactions among three groups for THA and TKA was not statistically different (P > 0.05).Conclusion: This study suggests that the combination of TDB patch and NSAIDs is safe and effective for postoperative analgesia after THA/TKA.